2018
DOI: 10.1002/lary.27082
|View full text |Cite
|
Sign up to set email alerts
|

Detection on pharyngeal wall floppiness in patients with nonstructural factor‐induced obstructive sleep apnea‐hypopnea syndrome: Difference in position detection

Abstract: 3b Laryngoscope, 128:2200-2205, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…15 Other factors such as soft tissue tonicity, tongue muscle activation, and head posture are related to the patency of the upper airway during respiration. [16][17][18][19] Unlike the pharyngeal airway, the nasal airway, which consists of the nasal cavity and paranasal sinuses, is dimensionally stable and not affected during sleep because it is surrounded by bony structures. Nasal obstruction has been designated as a risk factor for OSA, 1,5 and a computational fluid dynamics (CFD) study suggested that the turbulence of airflow created in the nasal cavity had a significant effect on the development of pharyngeal obstructions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other factors such as soft tissue tonicity, tongue muscle activation, and head posture are related to the patency of the upper airway during respiration. [16][17][18][19] Unlike the pharyngeal airway, the nasal airway, which consists of the nasal cavity and paranasal sinuses, is dimensionally stable and not affected during sleep because it is surrounded by bony structures. Nasal obstruction has been designated as a risk factor for OSA, 1,5 and a computational fluid dynamics (CFD) study suggested that the turbulence of airflow created in the nasal cavity had a significant effect on the development of pharyngeal obstructions.…”
Section: Introductionmentioning
confidence: 99%